Observation of field-induced single-ion magnet behavior in an octahedral dysprosium complex with a strong ligand field. (20th January 2021) - Zhang, Chunyang; Liu, Mengyao; Cai, Xingwei; Chen, Lei; Liu, Yuan-Zhong; Cui, Huihui; Zhang, Shao-Liang; Yuan, Aihua
Abstract : A mononuclear six-coordinate Dy III complex exhibiting slow magnetic relaxation provides a rare case for octahedral lanthanide complexes with SMM behavior. Abstract : By employing oxygen-containing ligands with strong coordination ability, a mononuclear six-coordinate Dy III complex [Dy(Ph3 PO)3 (OPhCl2 NO2 )3 ] (1 ) (Ph3 PO = triphenylphosphine oxide, Cl2 NO2 PhOH = 2, 6-dichloro-4-nitrophenol) with an octahedral DyO6 coordination environment has been successfully synthesized. Magnetic measurements reveal that complex 1 exhibits field-induced slow magnetic relaxation with an energy barrier of 21.3 K, which provides a rare case for mononuclear octahedral Ln-based complexes with slow magnetic relaxation behavior.